Novel Triterpenoid Alkaloids With Their Potential Cytotoxic Activity From the Roots of Siraitia grosvenorii - Wang, Huijuan; Ma, Guoxu; Wang, Huaxiang; Li, Lingyu; Dong, Aijun; Liu, Huiping; Huo, Xiaoshuang; Si, Jianyong; Wang, Junchi (Frontiers in Chemistry, 2022)
Four novel triterpenoid alkaloids, siragrosvenins A–D (1–4), and two new cucurbitane-type triterpenoids, siragrosvenins E–F (5, 6), together with eight known analogs (7−14), were isolated from the roots of Siraitia grosvenorii. Compounds 1−4 possessed a rare cucurbitane-type triterpenoid scaffold, featuring an extra pyrazine unit via the Strecker reaction in the cucurbitane framework. Compound 5 displayed a 6/6/6/5/6/5-fused polycyclic ring system, with an uncommon fused furan and pyran ring in the side chain. All the structures were characterized by extensive spectroscopic analysis, including HRESIMS, NMR, and X-ray crystallographic data. It is worth noting that the DP4+ analysis method was applied for the first time to determine the absolute configurations of the trihydroxybutyl moiety in the side chain of compounds 1–4. In vitro cytotoxicity screening found that compounds 4, 8, 9, 13, and 14 exhibited remarkable cytotoxic activities against three cell lines with IC50 values ranging from 1.44 to 9.99 μM. Siragrosvenin D shows remarkable cytotoxic activity on MCF-7 cells. As a result, it inhibited the proliferation of MCF-7 cells and reduced their viability via the induction of G2/M phase arrest and significantly induced apoptosis in MCF-7 cells.